The legacy of the Greek Genius - Costa i Llobera, Miquel (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
The native tribe of the litle town of Ses Paysses reacts with hatred and violence in the presence of the strange Greeks. Nuredduna discovers in the fineness of spirit of the Melesigeno rhapsode that there is a new world that enriches his human condition. The large statue of Nuredduna, by Remigia Caubet, on Palma’s Paseo Marítimo, shows Nuredduna looking at the sea with her hand outstretched as if waiting for the arrival of the foreigner that will open her up to a new world of harmony, more universal, much more enriching than the short look that believes itself to be the owner of the immediate. This precious message from the poem by Miquel Costa i Llobera is clearly topical for Mallorca, for Spain, for Europe and for the world. All are tormented by nationalisms, by the strong migratory and immigration currents, by tourism, and, at the same time, stimulated by the philosophical call of Hegel’s universal man and by the Christian call to universal brotherhood. Costa’s poem is a beautiful and poetic call to know how to let ourselves be carried away by the dynamics of history that move us to overcome singularity and open ourselves to universality.